2004
DOI: 10.1074/jbc.m406775200
|View full text |Cite
|
Sign up to set email alerts
|

BAD Is a Pro-survival Factor Prior to Activation of Its Pro-apoptotic Function

Abstract: The mammalian BAD protein belongs to the BH3-only subgroup of the BCL-2 family. In contrast to its known pro-apoptotic function, we found that endogenous and overexpressed BAD L can inhibit cell death in neurons and other cell types. Several mechanisms regulate the conversion of BAD from an anti-death to a pro-death factor, including alternative splicing that produces the N-terminally truncated BAD S . In addition, caspases convert BAD L into a pro-death fragment that resembles the short splice variant. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…If true, this would support a model suggesting that all pro-death factors also have pro-survival 'day jobs' (Figure 1). Consistent with this idea, but contrary to the norm, endogenous Bax, Bak and Bad are potent anti-death (not pro-death) factors in some scenarios (Lewis et al, 1999;Fannjiang et al, 2003;Seo et al, 2004). For example, hippocampal neurons and spinal cord motor neurons in Bak-deficient mice, and their derived tissues, are significantly more susceptible to cell death triggered by excitotic agents and neurotropic viruses.…”
Section: 'Day Jobs' For Pro-death Mitochondrial Proteinsmentioning
confidence: 89%
See 1 more Smart Citation
“…If true, this would support a model suggesting that all pro-death factors also have pro-survival 'day jobs' (Figure 1). Consistent with this idea, but contrary to the norm, endogenous Bax, Bak and Bad are potent anti-death (not pro-death) factors in some scenarios (Lewis et al, 1999;Fannjiang et al, 2003;Seo et al, 2004). For example, hippocampal neurons and spinal cord motor neurons in Bak-deficient mice, and their derived tissues, are significantly more susceptible to cell death triggered by excitotic agents and neurotropic viruses.…”
Section: 'Day Jobs' For Pro-death Mitochondrial Proteinsmentioning
confidence: 89%
“…However, Bid also needs to be activated in cells by proteolytic cleavage or in vitro by detergent-induced conformational changes. In fact, a number of Bcl-2 family proteins are cleaved by caspases and other proteases to alter their functions (Cheng et al, 1997;Clem et al, 1998;Kirsch et al, 1999;Seo et al, 2004). Other BH3-only proteins, such as Bad, are suggested to directly bind and inactivate the anti-death Bcl-2 family proteins (Puthalakath et al, 1999;Cheng et al, 2001;Wei et al, 2001).…”
Section: The Executioner Mitochondrionmentioning
confidence: 99%
“…It is known that cleavage of several BCL-2 family proteins, including BCL-xL, by proteases during programmed cell death enhances or activates their pro-death function (33)(34)(35)(36)(37)(38)(39)(40). In the squid stellate ganglion, we showed previously that hypoxia induces proteolysis of native BCL-xL and that a proteolytic fragment of this protein produces large conductance channel activity when applied to mitochondrial membranes (24).…”
Section: Z-vad-fmk Inhibits Induction Of the Hypoxia Channel And Slowmentioning
confidence: 99%
“…For example, Bax, Bak and Bad can be antiapoptotic, 15,61,62 whereas Bcl-2 and Bcl-x L can promote cell death when their N-terminus is cleaved off. [63][64][65] An extensive analysis of Bak knockout mice revealed that Bak function is dependent on the cell type, the developmental stage and the specific death stimulus.…”
Section: Mitochondrial Factors Encoded By Virusesmentioning
confidence: 99%
“…This antideath function of Bad was gradually lost relative to matched controls over the next few weeks, but was repeatedly recovered by generating new cell lines (SY Seo and JM Hardwick, unpublished). 62 Similarly, cIAP1 function must be analyzed de novo (T-T Sheu and JM Hardwick, unpublished). However, by considering the nature of these compensatory mutations that permit survival and growth in the absence of antideath factors, we will likely learn about the underlying functions of viral antideath factors.…”
Section: Considering the Complexities And Caveatsmentioning
confidence: 99%